Effect of serum from Vitamin E-supplemented calves on Infectious Bovine Rhinotracheitis Virus replication - Reddy, P.G.; Morrill, J.L.; Minocha, H.C.; Frey, R.A. (Kansas Agricultural Experiment Station, 2012)
Blood serum from Holstein calves supplemented with vitamin E at levels of 2800 mg orally or 1400 mg by injection at weekly intervals inhibited replication of Infectious Bovine Rhinotracheitis Virus in tissue cultures. Supplementing typical calf diets with vitamin E may increase protection against pathogens, at a time when they are more vulnerable to problems such as respiratory diseases.
Keywords: Dairy; Serum; Vitamin E; Infectious Bovine Rhinotracheitis Virus; Respiratory disease